1995
DOI: 10.1016/0896-6273(95)90159-0
|View full text |Cite
|
Sign up to set email alerts
|

Ion fluxes associated with excitatory amino acid transport

Abstract: Flux of substrate and charge mediated by three cloned excitatory amino acid transporters widely expressed in human brain were studied in voltage-clamped Xenopus oocytes. Superfusion of L-glutamate or D-aspartate resulted in currents due in part to electrogenic Na+ cotransport, which contributed 1 net positive charge per transport cycle. A significant additional component of the currents was due to activation of a reversible anion flux that was not thermodynamically coupled to amino acid transport. The selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
614
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 524 publications
(659 citation statements)
references
References 24 publications
43
614
2
Order By: Relevance
“…This suggested that I L-PHE was thermodynamically uncoupled from the substrate flux. Similar findings with respect to the Cl Ϫ component of I L-PHE have been reported for the ASCT-1 amino acid exchanger (19) and glutamate transporters (20,21). DISCUSSION We have characterized a novel C. elegans amino acid transporter, AAT-9, that is a homologue of mammalian heteromeric amino acid transporter light chain subunits.…”
Section: Substrate-activated Ion Conductance Of Aat-9 Transportersupporting
confidence: 65%
“…This suggested that I L-PHE was thermodynamically uncoupled from the substrate flux. Similar findings with respect to the Cl Ϫ component of I L-PHE have been reported for the ASCT-1 amino acid exchanger (19) and glutamate transporters (20,21). DISCUSSION We have characterized a novel C. elegans amino acid transporter, AAT-9, that is a homologue of mammalian heteromeric amino acid transporter light chain subunits.…”
Section: Substrate-activated Ion Conductance Of Aat-9 Transportersupporting
confidence: 65%
“…The situation is not as clear for the pore-mediated uncoupled transport; however, several experimental results support the notion that accessory subunits are not involved in anion conduction by glutamate transporters. Coupled and uncoupled current components of heterologously expressed EAAT transporters differ little between distinct expression systems (9,45), and anion pores associated with distinct EAAT isoforms exhibit distinct pore properties (12). In SDS-or BN-polyacrylamide gels, only a single protein could be observed after expression and purification of hEAAT2 and ecgltP in Xenopus oocytes as well as in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…We performed experiments in two distinct external anion compositions to separate the current components of the stoichiometrically coupled transport of glutamate Na ϩ , H ϩ , and K ϩ from the pore-mediated anion conductance. In Cl Ϫ -based external solution, the conductance of the hEAAT2-associated anion channel is very small (9), and the Glu/Na ϩ /H ϩ /K ϩ current amplitudes can therefore be approximated to the difference between currents in the presence and absence of external glutamate substrate. The so-calculated current amplitudes are similar in magnitude and voltage dependence for WT and His-tagged hEAAT2 (Fig.…”
Section: His-tagged Heaat2 Transporters Exhibit Unaltered Functional mentioning
confidence: 99%
“…34 In addition to mediating secondary-active glutamate uptake, EAATs also function as anion channels. [35][36][37][38] The EAAT1 p.Pro290Arg variant decelerates a conformational change associated with Na þ binding, causing a decrease in glutamate transport rates and a significant increase in EAAT1-associated anion current amplitudes. 39 EAAT1 and EAAT2 have similar expression profiles (mainly expressed in astrocytes and localized to plasmalemma), share basic mechanisms of glutamate transport, and exhibit similar anion conduction properties.…”
mentioning
confidence: 99%